The tRNA‐like small noncoding RNA mascRNA promotes global protein translation. (19th October 2020) - Lu, Xinping; Huang, Jinliang; Wu, Sipeng; Zheng, Qian; Liu, Peipei; Feng, Huimin; Su, Xiaoqing; Fu, Haipeng; Xi, Qiaoran; Wang, Geng
Abstract: mascRNA is a small cytoplasmic RNA derived from the lncRNA MALAT1 . After being processed by the tRNA processing enzymes RNase P and RNase Z, mascRNA undergoes CCA addition like tRNAs and folds into a tRNA‐like cloverleaf structure. While MALAT1 functions in multiple cellular processes, the role of mascRNA was largely unknown. Here, we show that mascRNA binds directly to the multi‐tRNA synthetase complex (MSC) component glutaminyl‐tRNA synthetase (QARS). mascRNA promotes global protein translation and cell proliferation by positively regulating QARS protein levels. Our results uncover a role of mascRNA that is independent of MALAT1, but could be part of the molecular mechanism of MALAT1 's function in cancer, and provide a paradigm for understanding tRNA‐like structures in mammalian cells. Synopsis: tRNA‐like noncoding RNA mascRNA increases the cytosolic protein levels of multi‐tRNA synthetase complex (MSC) component glutaminyl‐tRNA synthetase (QARS) by interacting with it and promoting its stability, thereby upregulating global protein translation. mascRNA interacts specifically with QARS in the cytosol. Binding of mascRNA increases QARS stability and protein levels. Increasing QARS protein levels by mascRNA results in an upregulation of global protein translation. Abstract : tRNA‐like noncoding RNA mascRNA increases the cytosolic protein levels of multi‐tRNA synthetase complex (MSC) component glutaminyl‐tRNA synthetase (QARS) by interacting with it and promoting its stability, thereby upregulating global protein translation.